Editorial note - Assounga, Alain (African Journal of Nephrology, 2017)
As the official journal of the African Association of Nephrology (AFRAN), the African Journal of Nephrology (AJN) publishes research on kidney diseases by African and other researchers. AJN has reached a significant milestone in this first issue of Volume 20. This is the first issue which was prepared and published using our new web-based platform. We wish to take this opportunity to thank the editorial board, the reviewers and the authors for their role in the successful migration to the new platform. To mark this milestone, and to coincide with the March 2017 AFRAN/AFPNA Congress in Cameroon, we are delighted to publish a special article on the history of AFRAN by Professor Rashad Barsoum, one of the co-founders of AFRAN. Contributions to the success of AFRAN by the International Society of Nephrology, and by colleagues from Europe, America and Africa, are acknowledged. This is an illustrated story of our association told by its founding president, which is now immortalised in AJN. This issue also features an original article reporting on malignant kidney tumours in Port Harcourt, Nigeria. Nephroblastoma and renal cell carcinoma remain the leading kidney malignancies, as also reported worldwide. Finally, two interesting case reports conclude this issue: a case of IgG4-related nephropathy and a successful pregnancy in a patient on chronic haemodialysis. Alain G Assounga Editor-in-Chief